High density lipoprotein cholesterol and alcohol consumption: are they related?. (26th April 2021) - Santos, MR; Pereira, A; Sousa, JA; Mendonca, F; Monteiro, JP; Temtem, M; Sousa, AC; Rodrigues, M; Henriques, E; Ornelas, I; Drumond, A; Mendonca, MI; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: GENEMACOR Introduction: High density lipoprotein cholesterol (HDL-C) is known to be inversely related to coronary artery disease (CAD). Previous observational studies have consistently reported that individuals with moderate alcohol consumption have a lower risk of cardiovascular disease compared with that of nondrinkers and heavy drinkers. The beneficial effects of moderate drinking appear to be mediated in large part by alcohol-induced increases in HDL-C concentrations. Objective: To evaluate if a moderate alcohol consumption (30-50g a day) is associated with higher levels of HDL-C in coronary patients. Materials and methods: 1676 patients selected from GENEMACOR study population, with at least one > 75% coronary stenosis by angiography (median age 53.3 ± 7.9 years, 78.6% male, median HDL 43.0 ± 11.1 mg/dL). Population was divided according to the HDL level quartiles (1st quartile HDL < 35.3 mg/dL; 2nd quartile HDL 35.3 – 42 mg/dL; 3rd quartile HDL 42 – 49 mg/dL; 4th quartile HDL > 49 mg/dL). Population of the 1st and 4th quartiles (825 patients, median age of 53.3 ± 8.0 years and 78.7% male) were adjudicated and prospectively followed-up by 5.0 ± 4.2 years. X2 and T student tests were used to analyze the demographic, laboratorial, angiographic and anthropometric characteristics of the population. Results: 420 (50.9%) patients were included in the 1st quartile group (median age 53.2 ± 7.9 years, 85.7% men) and 405 (49.1%) patients were included in the 4th quartile group (median age 53.4 ± 8.0 years, 71.4% men). The mean HDL level was higher in the population with moderate alcohol consumption (mean HDL 43.7 ± 15mg/dL in patients with alcohol consumption <30g/day, mean HDL 48.8 ± 16mg/dL in patients with moderate alcohol consumption and mean HDL 41.6 ± 15mg/dL in patients with alcohol consumption >50g/day). From 104 (median age 51.9 ± 7.9 years, 96.2% male) patients with a moderate alcohol consumption, 62.5% vs 37.5% were in 4th HDL quartile, p 0.01. Conclusion: We conclude that in our population, a moderate alcohol consumption is associated with higher levels of HDL-C. However, even if there is a causal association between alcohol consumption and higher HDL cholesterol levels, it is suggested that efforts to reduce coronary heart disease risks concentrate on the control of another risk factors.